Depressive State in the Emergency Department During COVID-19: A National Cross-Sectional Survey in China - Liu, Shuang; Han, Wei; Shen, Chenyu; Zhu, Changju; Wang, Qiaofang; Liang, Xianquan; He, Xiangxi; Xie, Qin; Wei, Jie; Wu, Miao; Zhao, Xiaodong; Liu, Hongsheng; et al. (Frontiers in Psychiatry, 2021)
Chinese emergency department (ED) staff encountered significant mental stress while fighting the coronavirus disease 2019 (COVID-19) pandemic. We sought to investigate the prevalence and associated factors for depressive symptoms among ED staff (including physicians, nurses, allied health, and auxiliary ED staff). A cross-sectional national survey of ED staff who were on duty and participated in combating the COVID-19 pandemic was conducted March 1–15, 2020. A total of 6,588 emergency medical personnel from 1,060 hospitals responded to this survey. A majority of respondents scored above 10 points on the PHQ-9 standardized test, which is associated with depressive symptoms. Those aged 31–45, those working in the COVID-19 isolation unit, and those with relatives ≤ 16 or ≥70 years old at home all had statistically significant associations with scoring >10 points. Depressive symptoms among Chinese emergency medical staff were likely quite common during the response to the COVID-19 pandemic and reinforce the importance of targeted ED staff support during future outbreaks.